Sweatshop : the history of an American idea - Hapke, Laura (New Brunswick, N.J. : Rutgers University Press, 2004)
Arguing that the sweatshop is as American as apple pie, Laura Hapke surveys over a century and a half of the language, verbal and pictorial, in which the sweatshop has been imagined and its stories told. Not seeking a formal definition of the sort that policymakers are concerned with, nor intending to provide a strict historical chronology, this unique book shows, rather, how the "real" sweatshop has become intertwined with the "invented" sweatshop of our national imagination, and how this mixture of rhetoric and myth has endowed American sweatshops with rich a.
Narrating the shop -- A shop is not a home: dirt, ethnicity, and the sweatshop -- Surviving sites: sweatshops in the progressive era and beyond -- Newsreel of memory: the WPA sweatshop in the Great Depression -- The sweatshop returns: post-industrial art -- Spinning the shop -- Spinning the new shop: El Monte and the Smithsonian furor -- Nike's sweatshop quandary and the industrial sublime -- Watching out for the shop.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Sweatshops -- United States -- History; Sweating-system -- États-Unis -- Histoire; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Sweatshops; United States; Samfundsvidenskab -- Økonomi; History